TEACHERS ABOUT GIFTED STUDENTS – SURVEY IN POLISH SCHOOLS - Malyska, Aldona; Stanczak, Malgorzata; Piotrowski, Pawel (European Scientific Journal, ESJ, 2014)
This study discusses some part of the survey results which was realized among teachers working in various types of polish schools. The research is concerned with the manners by which the teachers understand notion such as ―gifted students‖, and their experiences in pedagogical work with pupils, which can be named as ―talented‖ and also their opinions about such students (especially the question of features of gifted pupils, which are perceived and valuated by the teachers). One of main conclusion is that most of the teachers, especially those with longer period of professional experience, perceives that gifted students are in categories of intellectual abilities such as skillful memorizing and high IQ level – generally: such abilities which are measured by psychometric tests. At the same time, the teachers gave less value to such abilities of their pupils, which can be defined as creative and of a special talent.